387 A Phase II, multicenter study of the safety and efficacy of LAG525 in combination with spartalizumab in patients with advanced malignancies. (9th November 2020) - Lin, Chia-Chi; Garralda, Elena; Schöffski, Patrick; Hong, David; Siu, Lillian; Martin, Miguel; Maur, Michela; Hui, Rina; Soo, Ross; Chiu, Joanne; Zhang, Tian; Ma, Brigette; et al.
Abstract : Background: Expression of LAG-3, an inhibitory immunoreceptor, has been linked to reduced T-cell proliferation and cytokine production. LAG525 is a humanized IgG4 anti-LAG-3 antibody which inhibits LAG-3 binding to MHC class II. Spartalizumab is a humanized IgG4 anti-PD-1 mAb which inhibits PD-1 binding with its ligands PD-L1 and PD-L2. Preclinical data have shown promising antitumor activity when blocking LAG-3 and PD-1. Methods: The Phase II part of the first-in-human study (NCT02460224 ) explored LAG525 + spartalizumab in patients with advanced/metastatic non-small cell lung cancer (NSCLC), cutaneous and non-cutaneous melanoma, renal cell carcinoma (RCC), mesothelioma, or triple-negative breast cancer (TNBC). The dose/schedule of LAG525 and spartalizumab was 400 mg IV Q3W and 300 mg IV Q3W, respectively. Half of patients with TNBC naïve to anti-PD-1/PD-L1 received LAG525 at 600 mg IV Q4W and spartalizumab at 400 mg IV Q4W. The primary endpoint was overall response rate (ORR) using RECIST v1.1. Results: As of June 1, 2020, 235 patients were enrolled in the Phase II part of the study, including patients with NSCLC (n=42), melanoma (n=42), RCC (n=38), mesothelioma (n=57), or TNBC (n=56). In total, 142 patients were naïve to, and 93 patients were pretreated with, PD-1/PD-L1 inhibitors. Overall, 232 patients (99%) discontinued treatment, 76% due to progressive disease.ORR and disease control rate by indication and prior anti-PD-1/PD-L1 treatment are summarized below (table 1 ). Best overall response was 3 (1.3%) CR, 23 (9.8%) PR, 84 (35.7%) SD, 95 (40.4%) PD, and 30 (12.8%) unknown. For patients naïve to anti-PD-1/PD-L1, median progression free survival (mPFS) in months (90% CI) was 3.9 (1.7–5.6) for NSCLC, 2.2 (1.6–5.6) for melanoma, 4.4 (2.1–11.1) for RCC, 5.5 (3.5–6.4) for mesothelioma, and 1.9 (1.6–2.6) for TNBC. For patients pretreated with anti-PD-1/PD-L1, mPFS in months (90% CI) was 3.5 (1.9–4.9) for NSCLC, 1.9 (1.8–3.7) for melanoma, 3.0 (1.6–3.9) for RCC, 3.4 (1.8–3.8) for mesothelioma, and 1.7 (1.3–3.4) for TNBC. Adverse events of any grade, regardless of cause, were reported in 233 (99%) patients; the most common (occurring in >20%) were nausea (25%), fatigue (23%), and dyspnea (21%). Conclusions: LAG525 + spartalizumab exhibited antitumor activity across different indications, including patients with melanoma, RCC, and mesothelioma who had been pretreated with PD-1/-L1 inhibitors, suggesting that this combination may salvage prior PD-1/-L1 resistance. The combination was well tolerated, and no new safety signals were observed. Biomarker analysis is ongoing. Trial Registration: NCT02460224 Ethics Approval: This study was approved by an independent ethics committee or institutional review board at each site.